Quantum mechanical wavepacket calculations on chemical reactions - Russell, C (1998)
The quantum mechanical time-dependent wavepacket method is introduced in the context of the field of chemical dynamics. The theory of the method is presented for two processes of interest in dynamics: molecular photodissociation, and reactive scattering. For the first of these processes, an expression is derived for the absorption spectrum of a molecule undergoing an electronic bound-continuum transition. For the second process, a time-dependent formulation is obtained for the S-matrix, and the "flux formulation" for the calculation of initial state-selected reaction probabilities (ISSRPs) is shown to be equivalent to summing over appropriate S-matrix elements. The time-dependent wavepacket theory for molecular photodissociation is used in the calculation of the photodetachment spectrum of the FH̅₂ anion. Spectra are calculated for two different energy resolutions, and previously unobserved structure is seen in the higher resolution spectrum. The structure is assigned by studying energy-dependent wavefunctions corresponding to each peak in the spectrum. Some peaks are assigned to direct scattering states, while others are assigned to quantum mechanical resonance states localised in the reactant and product valleys of the potential energy surface. The implication of this is that a high-resolution photodetachment experiment may provide the first experimental evidence for resonances in the F + H2 reaction. For reactive scattering, the time-dependent wavepacket method is used (in conjunction with the rotationally adiabatic approximation for J > 0 calculations) to calculate ISSRPs for various initial states of the nearly-thermoneutral ionmolecule reaction: N+(3P)+H2(1Σ+g)→NH+(X2II)+H(2S). Dense resonance structure in the reaction probabilities for J = 0 is attributed to the influence of the deep wells in. the potential energy surface for the reaction. The ISSRPs are used to calculate initial state-selected cross sections and rate constants which are compared with the results of some earlier trajectory calculations and with experimental data. The implications of the results for the astrophysical significance of the reaction are discussed.